PP.13.26: CARDIAC PRO-INFLAMMATORY CYTOKINES, NO SYSTEM AND OXIDATIVE STRESS IN A FETAL PROGRAMMING MODEL OF HYPERTENSION INDUCED BY MODERATE ZINC DEFICIENCY SINCE FETAL LIFE. (June 2015) - Arranz, C.; Juriol, N.; Gobetto, N.; Pineda, G.; Garrido, F. Mendez; Wenk, G.; Carranza, A.; Elesgaray, R.; Toblli, J.; Tomat, A.
Abstract : Objective: Moderate zinc deficiency during intrauterine and postnatal growth is a fetal programming model of hypertension, renal and cardiovascular dysfunction. Male zinc deficient rats showed reduced left ventricular (LV) wall thickness and ejection fraction. The aim of this study was to evaluate, nitric oxide (NO) system, pro-inflammatory cytokines and oxidative state in LV of adult male rats exposed to this deficiency. Design and method: Wistar rats received during pregnancy up to weaning low (L:8 ppm) or control (C:30 ppm) zinc diet. After weaning, male offspring fed low (l) or control (c) zinc diet during 60 days (Cc, Ll, Lc). At day 81, we evaluated in LV: Interleukin-6 and Tumor Necrosis Factor-α (IL-6, TNF-α), basal NO synthase (NOS) and endothelial (eNOS), neuronal (nNOS) and inducible (iNOS) isoforms activities; eNOS and Ser1177 eNOS phosphorylation protein expression (eNOS/β-actin, pSer1177eNOS/eNOS), mRNA expression (eNOS/GAPDH) and lipid peroxidation end products levels (TBARS). Values are means ± SEM, n = 6/group. One way ANOVA, Bonferroni post-test. Results: *p < 0.01vs Cc; †p < 0.01vs Ll. NO production is mainly produced by eNOS, because basal NOS activity was not affected by nNOS and iNOS inhibitors, but was decreased by blocking Ca2+-calmodulin in all groups. Figure. No caption available. Conclusions: Zinc deficiency during fetal and postnatal life programs a lower production and bioavailability of cardiac NO due to decreased activity and pSer1177 of eNOS and increased oxidative stress. Oxidative stress and NO impairment, jointly with higher levels of pro-inflammatory cytokines, could contribute to the cardiac disorders observed in adult males. Adequate zinc diet after weaning was unable to totally avoid the cardiac alterations induced during fetal life.